Impact of E-Records as Evidence in the Judicial System under the Bharatiya Sakshya Adhiniyam 2023 - Vratika Singh; Bindu Jindal; Vishant Saini; Pranav Ranga; Rakhee Rani; Hardik Gupta; Minakshi Banger (Metallurgical and Materials Engineering, 2025)
The Bharatiya Sakshya Adhiniyam 2023 (BSA) is a revolutionary change in India’s legal landscape by making electronic records (e-records) admissible evidence, bringing them at par with conventional documentary evidence. By extending the definition of "documents" to cover digital records, the BSA deals with the challenges of the digital era, i.e., authenticity, chain of custody, and cybersecurity. Aiding provisions such as Section 61 prohibit denial of admissibility of electronic records on the basis of being electronic only, and Section 63 adds a uniform process of certification with expert authentication. These reforms simplify judicial procedures, minimize procedural challenges, and increase the efficiency of dealing with e-evidence cases. It is practical difficulties in terms of infrastructure deficiency, technical support, and privacy issues that lie at the root of complete implementation. This abstract examines the implications of e-records under the BSA on India’s judicial system and emphasizes the imperative of ongoing technological incorporation and policy reforms to attain equity and reliability in legal proceedings